THE EFFECT OF THE FLIPPED CLASSROOM LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN INDONESIAN GRADE IV AT MIS HIDAYATUL MUHAJIRIN PALANGKARAYA - Fathul Jannah; Rahmad; Sri Normuliati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of the Flipped Classroom model on the learning outcomes of Indonesian language in grade IV at MIS Hidayatul Muhajirin. In this model, students learn basic materials at home through videos/learning materials, while face-to-face time is focused on discussions and application exercises. The study was carried out because the learning outcomes, especially the capacity to speak and present, were still low. The study uses a quantitative approach with a quasi-experimental design of Nonequivalent Control Group Design through pretest-posttest. The results of the study are expected to present learning alternatives that are able to intensify student motivation, activeness, and learning outcomes.